A COMPARATIVE STUDY ON THE IN VITRO ANTI-DIABETIC PROPERTIES OF FOUR PLANTS FREQUENTLY USED TO TREAT DIABETES IN SOUTH AFRICA. - Koekemoer, T.; van de Venter, M.; Roux, S. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Medicinal plants are often used as adjunctive therapy with conventional medications, raising the possibility for synergistic or antagonistic interaction. Since numerous therapeutic targets are exploited to treat diabetes, knowledge on the mechanism by which herbal extracts exert their effect would be beneficial when traditional medicine is combined or used as an alternative to conventional drugs. Ethnobotanical surveys conducted in South Africa indicate that Artemisia afra, Ruta graveolens, Sutherlandia frutescens and Leonotis spp. are the most popular plants used to treat diabetes, however their precise mechanism of action is unknown. Various in vitro models designed to simulate specific therapeutic targets were used to screen plant extracts for potential anti-diabetic activity. The assays included alpha-glucosidase inhibition, DPPIV inhibition, antioxidant activity, glucose uptake and PPAR-gamma agonist activity. In addition, potential hepatotoxicity was assessed using HepG2/C3A cells. None of the plants showed any significant alpha-glucosidase inhibitory activity nor could they significantly stimulate adipocyte differentiation. The antioxidant capacity of the different plant extracts varied depending on the assay used. A. afra and S. frutescens had the best metal chelating and oxygen radical scavenging activity while only R. graveolens showed H2O2 scavenging activity. Both aqueous and ethanolic extracts prepared from S. frutescens demonstrated DPPIV inhibition, however the concentration required to achieve 50% inhibition suggests that this activity has little physiological relevance. Except for A. afra, none of the plants were toxic to cultured hepatocytes even at a concentration as high as 1 mg/ml. Further studies are required to identify the metabolic targets of these plants.